Psychosocial factors and T lymphocyte counts in Brazilian peacekeepers (Clinics, 2015)
OBJECTIVE: To investigate the associations between psychosocial factors and peripheral blood CD4 and CD8 T lymphocyte numbers in Brazilian peacekeepers. METHODS: Venous blood was collected from 759 peacekeepers who had just returned from a peace mission in Haiti. Among the 759 soldiers, 642 individuals completed the psychosocial measures. CD4 and CD8 T lymphocyte counts were measured by flow cytometry using a commercially available kit. Psychosocial factors, including military peace force stressors, clinical stress, anxiety and depression, were recorded. As a reference for T lymphocyte numbers, we measured T lymphocyte counts in 75 blood donors from the Instituto de Biologia do Exército, Rio de Janeiro. RESULTS: The median numbers of CD4 and CD8 T lymphocytes in the blood donors were 819 cells/µl and 496 cells/µl, respectively, with a CD4:CD8 ratio of 1.6. Significantly (p